Implementation Policy of The Arrangement and Formation of Modern Shop that Requires for Partnerships with Small and Medium Micro Enterprises (UMKM) Based on Perda No.12 of 2017 in Kudus Regency - Atik Noer Chalimah (Jurnal Daulat Hukum, 2018)
This research was made based on the Government Regulations of the Kudus Regency issuing Regional Regulation No. 12 of 2017 concerning Modern Store Arrangement and Guidance roomates requires Modern Stores to establish partnerships with the Small and Medium Micro Enterprises (UMKM), as well as discussing the operational hours items, namely the people of Kudus Regency who have implemented a a policy of obligation to establish partnerships between Several modern stores Small and Micro Businesses and intermediate so that in this thesis to find out the factors that Become obstacles and how the District Government's Strategic Efforts in developing Small and Medium Micro Enterprises. This research uses descriptive type or types of research. Descriptive research is a type of research that describes the findings of variables in the field that do not require a hypothesis scale. So its nature only illustrates and describes the findings in the field. The results of this study are based on interviews with the District Office of the Kudus Industry, the Department of Trade in the District of Kudus, and the empowerment of Micro Small and Medium Enterprises.Keywords: Implementation; Empowerment of Micro Small and Medium Enterprises; Public Policy; Modern Stores.